Effects of Management Issues in Business and Organisational Communication: A Study of Information and Communication Technologies (ICTs) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
The study sought to investigate the role and benefits of information communication technologies in organisational communication and the challenges of business and organisational communication and how to tackle these challenges with ICTs. The study is anchored on Two-way symmetrical model of public relations propounded by Grunig and Hunt in 1984.Library research method was adopted to generate data for the study. Findings revealed that, ICTs facilitate faster, wider and cost- saving communication which has been made possible by video conferencing. ICTs are used in managing relationships between an organisation and its various stakeholders using strategies like omnichannel, personal selling and customer- centric marketing. Managing and storing organisational data is another benefit of using ICTs in business and organisational communication, with cloud saving organisations can have their document stored digitally without need for large rooms for record and file cabinets. ICTs are also used to enhance operational efficiency by streamlining and optimizing business operations. Finding further revealed that, ICTs facilitate data-driven decision making by providing originations with data to make decisions geared towards customer satisfaction, this is so in that, data has become the lifeblood of modern businesses and an essential asset for informed decision-making. Findings revealed that, not listening to the communicator in a communication situation, inability to select the right word or the use of grandiloquent and outdated words, inconsistent communication channels and lack of employee engagement or low employee engagement were all challenges with business and organisational communication. It was concluded that, organisations need to use and continue to use ICTs to build relationships with their various customers and that ICTs have made immediate feedback possible and this is in line with the major tenet of Two-way Symmetrical Model which is centered on feedback. It was recommended among others that, the use of ICTs in business and organisational communication in the 21st century should not be relegated to the background because it is important for gathering data and making informed decisions.
Keywords: Business; Managing; Organisation; Communication; ICTs